TAHLIL THARIQAH AT-TADRIS ALMUSTAKHDAMAH FII MADDATIL MUTHALAAH - Wahyuni Simarmata (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
Analysis of Mutholaah Learning Methods at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun this research is qualitative by Descriptive methode according to Miles and Huberman’s teory. The objectives of this research are 1) to find out how the mutolaah learning method at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun, 2) to find out the supporting factors, 3) to find out the inhibiting factors in mutolaah learning at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun. The results of this study are 1) that the method used in teaching mutholaah i at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun is a combined method, where the teacher uses several methods in teaching mutholaah, such as reading, discussion, drama, memorizing and direct methods. 2) Supporting factors in mutholaah learning at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun are the existence of an Arabic-language environment, holding of language activities such as conversations, language improvement, equipped with media for reading such as wall magazines and hanging boards. 3) The inhibiting factors in learning mutholaah at two E of MTS Islamic Boarding School of Al-Kautsar Simalungun are that the methods used in learning do not yet support the improvement of students' writing abilities, and the students' use of Arabic does not comply with the correct Arabic rules in their daily conversations day.